2017
DOI: 10.1071/bt16170
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical native grasslands may not require fire, mowing or grazing to maintain native-plant diversity

Abstract: The rarity of native grasslands in agricultural districts heightens the requirement for optimal management to maintain diversity. Previous studies have suggested that disturbance is required to maintain species diversity in temperate Australian grasslands, but grasslands in semiarid environments do not have the same disturbance requirement. The current study examines the short-term responses to disturbance of subtropical grassland of the Darling Downs, south-eastern Queensland. We also compare temperate and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Declines in mowing and haymaking over the past century have reduced biodiversity in regions where mowing has been integral to the historical management of semi‐natural grasslands (e.g., several hundred years in Asia and over a thousand years in Europe; Baoyin et al., ; Feurdean et al., ; Koyama, Koyanagi, Akasaka, Takada, & Okabe, ; Pärtel, Helm, Reitalu, Liira, & Zobel, ). Few studies have quantified the effect of mowing on biodiversity in Australian grasslands (Fensham et al., ; Lewis et al., ; Morgan, ; Verrier & Kirkpatrick, ). The distribution of temperate grasslands in Australia is controlled predominantly by soil and climate (Lunt, Prober, & Morgan, ) but, prior to European colonization, their composition was maintained by native herbivore grazing and burning (ignited by lightning or Aboriginal people; Lunt & Morgan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Declines in mowing and haymaking over the past century have reduced biodiversity in regions where mowing has been integral to the historical management of semi‐natural grasslands (e.g., several hundred years in Asia and over a thousand years in Europe; Baoyin et al., ; Feurdean et al., ; Koyama, Koyanagi, Akasaka, Takada, & Okabe, ; Pärtel, Helm, Reitalu, Liira, & Zobel, ). Few studies have quantified the effect of mowing on biodiversity in Australian grasslands (Fensham et al., ; Lewis et al., ; Morgan, ; Verrier & Kirkpatrick, ). The distribution of temperate grasslands in Australia is controlled predominantly by soil and climate (Lunt, Prober, & Morgan, ) but, prior to European colonization, their composition was maintained by native herbivore grazing and burning (ignited by lightning or Aboriginal people; Lunt & Morgan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the disturbance requirement for maintaining alpha diversity might not be ubiquitous across the range of grasslands. Indeed, in subtropical grasslands, no change in native richness was found when mowing and fire were introduced in previously undisturbed sites, likely due to lower rates of biomass accumulation compared to temperate grasslands (Fensham et al 2017). Introducing disturbance into undisturbed sites also increased exotic richness (Kirkpatrick 1986; Smith et al 2018), but most studies did not explore this (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, phytomass accumulation does not follow a linear function of time-sincedisturbance, i.e. it is decoupled from disturbance (Fensham et al 2017). Lewis et al (2008Lewis et al ( , 2010 found in arid (Astrebla) grasslands, with a highly variable climate, that recent rainfall events were far more important for sward density than disturbance.…”
Section: Phytomass Accumulation Is Governed By Multiple Drivers;mentioning
confidence: 99%
“…In subtropical and semiarid ecosystems, low biomass accumulation might reflect high decomposition rates (Fensham et al 2017) or erratic production (e.g. tied to above-average rainfall; Austin and Williams 1989).…”
Section: Phytomass Accumulation Is Governed By Multiple Drivers;mentioning
confidence: 99%